Harmful effects of fluorine compounds on agricultural crops - Samatov Ilhom; Umirov Javokhir; Akhmedov Khasan; Narboyev Zafar (BIO Web of Conferences)
Environmental problems such as environmental changes, soil, water and atmospheric air pollution and depletion of biological resources are observed in the world as a result of economic and technical development of countries, growth of production rate, population growth. In particular, as a result of the increase of industrial waste, its negative impact on atmospheric air pollution, the amount of CO2, N2O, CH4 gases and fluorine compounds in the biosphere is increasing year by year. The abundance of fluorine compounds in agricultural products leads to a decrease in the quality of products. The obtained results revealed that trees such as quince, vine, peach, apricot have a high degree of drying from the edges of the leaves compared to the control.